Protein Flexibility in Drug Discovery: From Theory to Computation. Issue 7 (17th April 2015) - Buonfiglio, Rosa; Recanatini, Maurizio; Masetti, Matteo
Abstract Nowadays it is widely accepted that the mechanisms of biomolecular recognition are strongly coupled to the intrinsic dynamic of proteins. In past years, this evidence has prompted the development of theoretical models of recognition able to describe ligand binding assisted by protein conformational changes. On a different perspective, the need to take into account protein flexibility in structure‐based drug discovery has stimulated the development of several and extremely diversified computational methods. Herein, on the basis of a parallel between the major recognition models and the simulation strategies used to account for protein flexibility in ligand binding, we sort out and describe the most innovative and promising implementations for structure‐based drug discovery.